A Systematic Review of Factors Influencing Citizen Engagement in Smart Cities: Is a New Paradigm Needed? - Mahboubeh Kahvand; Ali Shayan; Shaban Elahi; Iman Raeesi Vanani (Iranian Journal of Information Processing & Management)
While the primary goal of smart cities is to create a better quality of life for urban residents, some researchers believe that this goal has largely remained as a slogan, and the objectives of smart cities are more aligned with and in favor of the interests of other stakeholders such as governmental institutions and private companies. Even in cases where citizen-centric approaches have been emphasized and implemented, it is observed that citizens are merely users of smart city services or only act as sensors in the city, without playing a role in shaping and creating initiatives for participation in the governance of their cities. Taking these challenges into account in the realm of smart city management, transforming the management models of smart cities is imperative. In this article, through a systematic literature review using the PRISMA protocol, we identified the different roles of citizens and factors influencing citizen participation in smart cities. Finally, we address the question of whether the current trend indicates a lack of creative involvement and real participation of citizens in smart city projects, and whether there is a need to introduce a new paradigm for the evolution of the idea of a smart city. We believe that there is indeed a need for this new paradigm, which we have termed the Responsive Smart City.